Training in Sync with the Cycle? The Impact of Hormonal Fluctuations During the Menstrual Cycle on Knee Joint Stability and ACL Injuries - Woźniakowska , Iga; Zambrzycka, Maja; Misarko, Aleksandra; Jedwabnik, Monika; Ścigała, Stanisław; Peszuk, Krzysztof; Dobrosielska, Adrianna; Krajewski, Hoang Viet; Olszewski, Bartosz; Lech, Weronika (Quality in Sport, 2026)
Background. Anterior Cruciate Ligament injuries represent a significant "epidemic" in sports medicine, disproportionately affecting female athletes. Women tear their ACL 2 to 10 times more often than men participating in the same sports. This disparity suggests that beyond anatomical and biomechanical differences, unique biological factors - specifically hormonal fluctuations and their impact on ligament structure - play a critical role in injury susceptibility. Aim. The aim of this study was to conduct an analysis of the publications from the last decade regarding the influence of the menstrual cycle, sex hormones and oral contraceptives on knee joint laxity and ACL injury risk. Material and methods. A comprehensive PubMed literature search (2014–2024) was conducted, only clinically relevant, English, free full-text articles were included, supplemented by foundational studies. Results. A total of 17 original studies were included, 4 review studies have been inspected for a better understanding of older research. The analysis confirms that the pre-ovulatory and ovulatory phases are associated with increased anterior knee laxity due to peak estrogen levels. However, recent evidence suggests that increased laxity does not always result in altered biomechanics in elite athletes due to neuromuscular compensation. Conclusions. Current evidence identifies the late follicular and ovulatory phases as the period of highest ACL injury risk, driven by a simultaneous decline in both passive joint stability and active motor control. Importantly, utilizing oral contraceptives does not offer a complete solution, as they only address passive laxity while leaving neuromuscular deficits unresolved and posing systemic risks. Future injury prevention must therefore adopt a multidimensional approach, utilizing individualized screening that integrates menstrual history, specific anatomical predispositions, and objective biomechanical assessments.